2012
DOI: 10.5012/bkcs.2012.33.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Dilute Two-Dimensional Ring Polymer Solutions

Abstract: Structure and Dynamics of dilute two-dimensional (2D) ring polymer solutions are investigated by using discontinuous molecular dynamics simulations. A ring polymer and solvent molecules are modeled as a tangent-hard disc chain and hard discs, respectively. Some of solvent molecules are confined inside the 2D ring polymer unlike in 2D linear polymer solutions or three-dimensional polymer solutions. The structure and the dynamics of the 2D ring polymers change significantly with the number (Nin) of such solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Recent computer simulations of a similar model founded this exponent located between 1.30 and 1.04 for similar model of rings of longer (consisting of up to N = 512 segments) at the polymer concentration φ = 0.05 and 1.0 respectively . Discontinuous molecular dynamics of two-dimensional rings with solvent molecules (at low solvent concentration φ = 0.16) showed that the exponent 2ν changes from 2.0148 (the maximum possible number of solvent molecules inside the chain contour) to 1.330 (no solvent molecules inside the chain contour); the latter value is quite close to our findings. It is worth mentioning that experiments on single circular DNA adsorbed on mica also founded the exponent 2 v = 1.5 …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent computer simulations of a similar model founded this exponent located between 1.30 and 1.04 for similar model of rings of longer (consisting of up to N = 512 segments) at the polymer concentration φ = 0.05 and 1.0 respectively . Discontinuous molecular dynamics of two-dimensional rings with solvent molecules (at low solvent concentration φ = 0.16) showed that the exponent 2ν changes from 2.0148 (the maximum possible number of solvent molecules inside the chain contour) to 1.330 (no solvent molecules inside the chain contour); the latter value is quite close to our findings. It is worth mentioning that experiments on single circular DNA adsorbed on mica also founded the exponent 2 v = 1.5 …”
Section: Resultsmentioning
confidence: 93%
“…These macromolecules can now be precisely synthesized and characterized. The structure of cyclic chains and their dynamics properties were the subjects of numerous experimental, theoretical, and simulation studies although the discussion about their properties is not closed yet. The two-dimensional polymer systems containing cyclic macromolecules were also a subject of experiments and theoretical considerations. , Computer simulations of strictly two-dimensional cyclic macromolecules and of strongly adsorbed three-dimensional rings were not so numerous. , They mainly showed that the adsorption of rings is considerably higher than that of linear and star-branched chains. The mobility of rings confined to a thin film was found to slow down during the annealing (or when the strength of the adsorption increases) and they were always slower than linear chains. , …”
Section: Introductionmentioning
confidence: 99%
“…In general, the conformation and dynamics of circular polymers is still a subject of considerable interest [36]. Current experimental capabilities reach even down to single molecule experiments [1], so that one might speculate on the possibility to observe a dynamical transition of the type elucidated here in appropriate non-equilibrium, 2D constrained settings [37].…”
mentioning
confidence: 99%